Sistem Informasi Layanan Administrasi Desa Berbasis Web pada Kantor Desa Ulak Kemang Baru - Pisgamargareta, Abel; Coyanda, John Roni; Yulianti, Evi (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study aims to design and develop a web-based village administrative service information system for the Ulak Kemang Baru Village Office. The system is designed as a solution to various issues faced in manual administrative services, such as slow document processing, inefficiencies in document management, and limited time and accessibility for the community. Through the web-based system, the community can submit administrative requests online, while village officials can manage data in a more structured and efficient manner. The software development method used is the Prototype method, which enables iterative system development involving user feedback. The system design process utilizes Unified Modeling Language (UML) for system modeling, while system implementation is carried out using PHP and MySQL. The system testing was performed using the blackbox method, which focuses on testing system functionality without considering internal implementation details. The results indicate that the information system can improve the efficiency and effectiveness of village administrative services. The system successfully provides key features such as user registration, document submission, verification by village officials, and report generation. Based on the testing results, all major system features function as expected according to user requirements. With this system, it is expected that administrative services at the Ulak Kemang Baru Village Office will become faster, more transparent, and easily accessible to the community, supporting the digitalization of public services at the village level.